2023
DOI: 10.3390/app13074399
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Conventional Non-Destructive Testing Methods in Detecting Embedded FRP Reinforcements

Abstract: Fiber-Reinforced Polymer (FRP) bars/strands are the most promising alternative to their steel counterparts for reinforcing concrete elements due to their resistance to corrosion, lighter weight, higher strength and better durability. However, very limited research has been conducted in relation to non-destructive testing (NDT) methods that are applicable to damage detection in FRP bars or the detection of FRP reinforcements embedded in concrete. The ability to assess the condition of the relatively new and uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Regarding the inability to detect damage in the BFRP bar in Slab P, further experiments need to be conducted on slab specimens only reinforced with BFRP bars (similar to Slab O) before coming to a conclusion about the detectability of damage in BFRP bars. The low frequency 1 GHz GPR device used in this research was not able to detect the BFRP bar but a previous study by the authors [ 36 ] has proved that it can be detected using higher frequency GPR devices. Future research on detecting damage in BFRP bars should focus on using high-frequency GPR devices to detect several types of simulated damage with variations in parameters such as depth, extent, and type of damage.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Regarding the inability to detect damage in the BFRP bar in Slab P, further experiments need to be conducted on slab specimens only reinforced with BFRP bars (similar to Slab O) before coming to a conclusion about the detectability of damage in BFRP bars. The low frequency 1 GHz GPR device used in this research was not able to detect the BFRP bar but a previous study by the authors [ 36 ] has proved that it can be detected using higher frequency GPR devices. Future research on detecting damage in BFRP bars should focus on using high-frequency GPR devices to detect several types of simulated damage with variations in parameters such as depth, extent, and type of damage.…”
Section: Discussionmentioning
confidence: 72%
“…This view represents a cross-section parallel to the scanned surface, which can be further developed into a comprehensive 3D iso-surface model. A previous study by the authors [ 36 ] can be further explored for in-depth information on the applicability of GPR and PAU techniques for the inspection of structural elements reinforced with FRP.…”
Section: Experimental Programmentioning
confidence: 99%
See 1 more Smart Citation
“…[32]. NDT methods have been increasingly used for quality control, quality assurance and quality assessment of both new and old structures [33][34][35]. Many NDT techniques, such as visual inspection (VT) [36,37], tap testing (TT) [38][39][40][41][42], impact echo testing (IE) [43][44][45][46][47], microwave testing (MW) [48][49][50][51][52][53], ground penetrating radar (GPR) [54][55][56][57][58], ultrasonic testing (UT) or phased array ultrasonic testing (PAU) [59][60][61][62][63][64], infrared thermography testing (IR) [56][57][58][59][60][61][62][63][64], acoustic emission testing (AE) [65][66][67][68], laser testing (LT) [69]…”
Section: Inspection Of Eb-frp Concrete Elementsmentioning
confidence: 99%
“…It was found that commercially available GPR devices can detect FRP, given that a higher penetrating wave frequency is applied. Regarding PAU, detecting glass fibers is unsatisfying, while localizing steel bars produces satisfactory results [ 15 ].…”
Section: Introductionmentioning
confidence: 99%